Perfil neurocognitivo de adolescentes com Dor Musculoesquelética Idiopática - Molina, Juliana [UNIFESP] (2010)
Introduction: Idiopathic musculoskeletal pain(IMP) had a negative impact on the quality of life of patients and relatives. Many patients are assessed from physical aspect, and proper attention is not given anymore to psychological aspects, specially stress, depression, and cognitive changes, among other characteristics. Objectives: 1) to assess memory functioning, and 2) to investigate aspects such as sleep, stress, depression, behavior, and quality of life in a sample of adolescents with idiopathic musculoskeletal pain.Methods: Nineteen adolescents with idiopathic musculoskeletal pain and twenty apparently healthy controls were assessed through investigative scales for humor, sleep, stress, and quality of life, in addition to a neuropsychological test battery. Results: The study sample consisted of girls (84%) predominantly, having not differences regarding socioeconomic status – level B2. The occurrence of depression symptoms and attention difficulties were not different between groups, where 26% of IMP patients had indicating scores for depression, the same for 30% of control group. Regarding quality of life, sleep, and stress, patients have demonstrated worse scores in relation to control group, and 78.95% of IMP adolescents had criteria for stress diagnosis, whereas only 35% occurred in control group adolescents. In both groups, observed scores classify adolescents as in resistance phase (intermediate) and exhaustion phase (pathological) of stress, and IMP group had more frequently symptomatic complaints in physical and emotional aspect. In the neurocognitive assessment, significant impairments on memory were not demonstrated. Conclusion: Adolescents with idiopathic musculoskeletal pain had not cognitive impairments as those noted in adults with musculoskeletal pain. However, our findings suggest intermediate to advanced stress experienced by these adolescents, with subsequent impairment on quality of life. Biopsychosocial interventions are of great importance to minimize chronic pain impact on quality of life and prognosis improvement.